Synthesis, Cytotoxic Analysis, and Molecular Docking Studies of Tetrazole Derivatives via N-Mannich Base Condensation as Potential Antimicrobials - Atef Hatamleh A; Al Farraj D; Salah Al-Saif S; Chidambaram S; Radhakrishnan S; Akbar I (Dove Medical Press, 2020)
Ashraf Atef Hatamleh,1 Dunia Al Farraj,1 Sarah Salah Al-Saif,1 SathishKumar Chidambaram,2 Surendrakumar Radhakrishnan,2 Idhayadhulla Akbar2 1Botany and Microbiology Department, College of Science, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Research Department of Chemistry, Nehru Memorial College (Affiliated with the Bharathidasan University), Puthanampatti, Tiruchirappalli District, Tamil Nadu, South IndiaCorrespondence: Idhayadhulla Akbar Email a.idhayadhulla@gmail.comPurpose: A new series of tetrazole derivatives, which are renowned antimicrobials possessing a five-membered aromatic heterocyclic group, are synthesized herein and subjected to antimicrobial and cytotoxicity screening.Methods: The tetrazole derivatives were synthesized via ultrasonication using Mannich base condensation. Structural verification of the products was performed using IR, 1H NMR, and 13C NMR spectroscopy, as well as mass spectroscopic and elemental analyses. The compounds were then screened for antimicrobial and cytotoxic activity against HepG2 (liver), MCF-7 (breast), and HeLa (cervical) cell lines. Inter- and intra-molecular binding interactions were determined using molecular docking studies. The exact binding mode between the most active tetrazole derivatives (ie, 1b, 2a, and 2b) and the proteins (ie, 4OR7, 1AI9, and 4FM9) was established using Autodock Vina 1.1.2 software and compared to the binding mode of the reference compounds (ie, cefazolin, clotrimazole, and fluorouracil).Results: Compound 1b was extremely active against Enterococcus faecalis relative to the positive control cefazolin. Compounds 1b and 1e were active against Candida albicans and Microsporum audouinii compared to the positive control clotrimazole in antifungal screening. The HepG2 (liver) and MCF-7 (breast) cancer cell lines were particularly susceptible to the synthesized compounds. Compared to the control compound fluorouracil, 2a and 2b were extremely active against all three cancer cell lines. Molecular docking studies showed that 2b exhibited higher binding affinity (− 7.8 kcal/mol) to the 4OR7 protein than the control cefazolin (− 7.2 kcal/mol).Conclusion: Generally, 1b, 2a, and 2b exhibited impressive inhibitory capabilities in antibacterial, antifungal, and cytotoxic screenings relative to the reference compounds. The results of the molecular docking studies and both the microbial and anticancer screenings indicate that these novel derivatives could be developed into potential therapeutic agents for medical applications.Keywords: antibacterial, antifungal, cytotoxic, molecular docking, N-Mannich base, ultrasonication